Alpha-synuclein null mutation exacerbates the phenotype of a model of Menkes disease in female mice - MegAnne Casey; Dan Zou; Renee A. Reijo Pera; Tiffany Hensley-McBain; Deborah E. Cabin (Frontiers in Neuroscience)
Human SNCA, which encodes a-synuclein protein (SNCA), was the first gene linked to familial Parkinson’s disease (PD). Since the discovery of the genetic link of SNCA to Parkinson’s nearly three decades ago, many studies have investigated the normal function of SNCA protein. However, understanding of the normal function of SNCA is complicated by the lack of a reliable mammalian model of PD; indeed, mice with homozygous null mutations in the Snca gene live a normal lifespan and have only subtle synaptic deficits. Here, we report the first genetic modifier (a sensitized mutation) of a murine Snca null mutation, namely the ATPase copper transporting alpha (Atp7a), an X-linked gene that escapes inactivation in both mice and humans. In humans, mutations in Atp7a are linked to Menkes disease, a disease with pleiotropic and severe neurological phenotypes. Atp7a encodes a copper transporter that supplies the copper co-factor to enzymes that pass through the ER-Golgi network; under some conditions, Atp7a protein may also act to increase copper flux across the cell membrane. Male mice that carry a mutation in Atp7a die within 3 weeks of age regardless of Snca genotype. In contrast, female mice that carry the Atp7a mutation, on an Snca null background, die earlier (prior to 35 days) at a significantly higher rate than those that carry the Atp7a mutation on a wildtype Snca background. Thus, Snca null mutations sensitize female mice to mutations in Atp7a, suggesting that Snca protein may have a protective effect in females, perhaps in neurons, given the co-expression patterns. This study adds to the growing literature suggesting that alterations in a-synuclein structure and/or quantity may manifest in neurological differences in males and females including phenotypes of developmental delays, seizures, muscle weakness and cognitive function.